2023
DOI: 10.2174/1573397118666220623105703
|View full text |Cite
|
Sign up to set email alerts
|

Case Report of Sotalol Induced IgA Vasculitis

Abstract: Background: IgA vasculitis is the most common form of systemic vasculitis in children but can occur in adults. Inciting antigens include infections, drugs, foods, insect bites, and immunizations. Antibiotics and tumor necrosis factor (TNF) alpha inhibitors are the most common class of drugs that cause IgA vasculitis. Although sotalol and rivaroxaban have been documented to cause leukocytoclastic vasculitis, we have never come across any literature attributing IgA vasculitis to either drug. Additionally, Rocky … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Sotalol-occlusion/occlusion-like syndrome can be the final endpoint for resolving mentioned discordances in the sotalol and antiarrhythmics effects [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]). Consequently, counteraction by BPC 157 therapy may be important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sotalol-occlusion/occlusion-like syndrome can be the final endpoint for resolving mentioned discordances in the sotalol and antiarrhythmics effects [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]). Consequently, counteraction by BPC 157 therapy may be important.…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong anti-arrhythmic effect (i.e., supraventricular arrhythmias, recurrent atrial fibrillation) long ago demonstrated [ 58 ], but also severe prolonged QTc interval prolongation, life-threatening ventricular arrhythmias, including polymorphous ventricular tachycardia or torsade de pointes [ 58 ] (while blood not properly pumped out of the heart, and thereby, pooling and forming a clot [ 8 ]). Long ago, there was a thrombolytic effect of beta blockers and sotalol, in particular [ 59 ], beta-blockers improve endothelial function [ 60 ], but sotalol-induced vasculitis [ 61 ] and diffuse intra-alveolar hemorrhage [ 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ig-A vasculitis is a childhood disease caused by inflammation of the small blood vessels (vasculitis) [1][2][3][4][5][6][7][8][9][10][11]. It can affect the skin, intestines, kidneys and joints.…”
Section: Discussionmentioning
confidence: 99%
“…The disease usually resolves within 4 weeks without late health effects. Purpura Schönlein-Henoch is the most common inflammatory vascular disease in young children and school-age children [1][2][3][4][5][6][7][8][9][10][11]. The disease always affects the skin.…”
Section: Discussionmentioning
confidence: 99%